Temporal Changes under the Influence of Digital Media - Gálik, Slavomír; Oprala, Branislav (Communication Today, 2021)
Current online communication disintegrates linear time and supports the simultaneous. Fast online communication also accelerates the ‘offline’ world – the world of business, transportation and so on. Thus, new temporal changes introduce disruption and desynchronisation of the old temporalities. The authors identify 4 risks caused by temporal desynchronisation: 1 – on the media level – desynchronisation between linear and simultaneous time. 2 – on the cognitive level – desynchronisation between fast time and limited cognitive capacity in humans. 3 – on the social level – desynchronisation between fast work time and slow time that we use for recreation, family life and so on. 4 – on the environmental level – desynchronisation between the fast economy and the slow regeneration of natural resources. The authors see a solution in antitemporalities, i.e. the ability to slow down fast time and switch between various time rhythms. However, we need to systematically learn how to use these anti-temporalities. The authors believe that the human mind needs quality cognitive training to be capable of slowing down and speeding up and thus switch efficiently between different time modes.